Women and citizenship: The achievement of women’s suffrage in Peru (1933-1955) - Poulsen, Karen (2016)
The enactment of women’s suffrage positioned Peru within the group of modern nations. President Odría and his wife are usually seen as its precursors, although they were not. However, they gave it a political use. Odría meant to legitimizehis image and that of his governmental environment. María de Odría was nominated for mayor under the law. In contrast, this study attributes the obtainment of women´s vote to the pressure on the undemocratic government ofOdría and to the emergence of successful women, professionals and workers, who changed the scenery of androcentric spaces.